THE INFLUENCE OF PROBLEM BASED LEARNING (PBL) MODELAND LEARNING MOTIVATION ON CRITICAL THINKING ABILITYIN GRADE 6 SDN 14 TANJUNG MEDAN - Timbul Amar Hotib; Deny Setiawan; Tappil Rambe (SENSEI RESEARCH CENTER, 2022)
This study aims to determine: (1) The effect of the Problem Based Learning (PBL) learning model on the critical thinking skills of Class VI students of SD Negeri 14 Tanjung Medan in the 2021/2022 academic year; (2) The effect of learning motivation on students' critical thinking skills; (3) The interaction effect of Problem Based Learning (PBL) learning model and learning motivation on students' critical thinking skills. The sampling technique in this study was carried out in two classes, 36 students in class VI1 as an experimental class with Problem Based Learning (PBL) learning model and class VI2 as a control class with 32 students taught using the Direct Instruction learning model. Data collection instruments using: (1) motivation questionnaire in the form of a statement as many as 30 items; (2) Critical thinking test in the form of multiple choice as many as 15 items. This research method is quasi-experimental with data analysis techniques using the 2-way Anova test with a significant level of = 0.05. The results of this study showed that: (1) There is an influence of learning motivation on students' critical thinking; (?=0.05, p=0.000); (2) There is an effect of learning model on students' critical thinking; (?=0.05, p=0.008); (3) There is an interaction between the learning model and learning motivation towards critical thinking; (?=0.05, p=0.012).